OCCURRENCE AND ORIGIN OF BARYTE MINERALIZATION IN THE BENUE TROUGH, NIGERIA: A REVIEW - AUWALU D.; DASPAN R. I.; MBORINGONG M. N.; ABUBAKAR U. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
In this paper, a review of the available information on the occurrences, structural control, grade, genesis and possible economic importance of Baryte resources in the Benue Trough was attempted. Baryte mineralization in Nigeria is known to occur as disseminated nodules of swarms of veins (fracture in filling) that extended to deeper parts of the Precambrian Basement Complex along with the Cretaceous sediments of the Benue Trough. The mineralization is hydrothermal in origin that is usually associated with base metals, quartz, siderite, marcasite and pyrite, as gangue. Baryte mineralization in the trough is structurally controlled by NW-SE, NE-SW, N-S and E-W trends and believed to have formed from the brine springs and connate waters that pressed out during tectonic compaction and also chemical interaction between the rising metal bearing hydrothermal fluid with the surrounding country rocks. The host lithologies varied from sandstones, shales, siltsone, limestone, conglomeratic ironstone to metasediments and granitoids. Most of the Barytes veins in the Benue Trough meets the API specification of specific gravity of 4.2 and the BaO of 92.0 wt. % used for drilling mud in the oil industry while fewer veins that portrayed low quality require beneficiation and upgrading for quality improvement.